Proceedings of the 18th ACM Conference on Computer and Communications Security 2011
DOI: 10.1145/2046707.2046732
|View full text |Cite
|
Sign up to set email alerts
|

Stealthy traffic analysis of low-latency anonymous communication using throughput fingerprinting

Abstract: Anonymity systems such as Tor aim to enable users to communicate in a manner that is untraceable by adversaries that control a small number of machines. To provide efficient service to users, these anonymity systems make full use of forwarding capacity when sending traffic between intermediate relays. In this paper, we show that doing this leaks information about the set of Tor relays in a circuit (path). We present attacks that, with high confidence and based solely on throughput information, can (a) reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 32 publications
(44 reference statements)
0
74
0
Order By: Relevance
“…Our method assumed that the adversaries were in a position to perturb the victim traffic by colluding with the server, and are in control of various network vantage points, from where they can remotely observe variations in network bandwidth. Mittal et al [16] demonstrated a modified version of the Murdoch and Danezis' attack that relies on path bandwidth variation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method assumed that the adversaries were in a position to perturb the victim traffic by colluding with the server, and are in control of various network vantage points, from where they can remotely observe variations in network bandwidth. Mittal et al [16] demonstrated a modified version of the Murdoch and Danezis' attack that relies on path bandwidth variation.…”
Section: Related Workmentioning
confidence: 99%
“…tacker could follow a more focused approach by employing existing techniques [7,16] to identify the actual relays used by the victim's circuit, and only monitor those.…”
Section: Approachmentioning
confidence: 99%
“…Most of the research on Tor has focused on techniques aimed at degrading user's anonymity by means of congestion attacks (Evans et al [7], Murdoch and Danezis [19]), web page fingerprints (Shi and Matsura [23]), observations of the throughput of Tor streams (Mittal et al [16]), or by means of colluding nodes (Fu et al [9], Levine et al [14]). Other attacks study the potential threat of a (semi) global adversary (Murdoch and Zieliński [17], Edman and Syverson [6], Chakravarty et al [3]), although this does not fit into Tor's original adversary model.…”
Section: Related Workmentioning
confidence: 99%
“…For example, several attacks have been proposed [12,17,24,27] that rely on measuring the latency or throughput of a Tor circuit to draw inferences about its source and destination. If an algorithm improves the throughput or responsiveness of Tor circuits this can improve the accuracy of the measurements used by these attacks either directly or by averaging a larger sample.…”
Section: Introductionmentioning
confidence: 99%